Potential genetic causes of miscarriage in euploid pregnancies: a systematic review. (31st May 2019) - Colley, Emily; Hamilton, Susan; Smith, Paul; Morgan, Neil V; Coomarasamy, Arri; Allen, Stephanie
Abstract: BACKGROUND: Approximately 50% of pregnancy losses are caused by chromosomal abnormalities, such as aneuploidy. The remainder has an apparent euploid karyotype, but it is plausible that there are cases of pregnancy loss with other genetic aberrations that are not currently routinely detected. Studies investigating the use of exome sequencing and chromosomal microarrays in structurally abnormal pregnancies and developmental disorders have demonstrated their clinical application and/or potential utility in these groups of patients. Similarly, there have been several studies that have sought to identify genes that are potentially causative of, or associated with, spontaneous pregnancy loss, but the evidence has not yet been synthesized. OBJECTIVE AND RATIONALE: The objective was to identify studies that have recorded monogenic genetic contributions to pregnancy loss in euploid pregnancies, establish evidence for genetic causes of pregnancy loss, identify the limitations of current evidence, and make recommendations for future studies. This evidence is important in considering additional research into Mendelian causes of pregnancy loss and appropriate genetic investigations for couples experiencing recurrent pregnancy loss. SEARCH METHODS: A systematic review was conducted in MEDLINE (1946 to May 2018) and Embase (1974 to May 2018). The search terms 'spontaneous abortion', 'miscarriage', 'pregnancy loss', or 'lethal' were used to identify pregnancy loss terms. These were combined with search terms to identify the genetic contribution including 'exome', 'human genome', 'sequencing analysis', 'sequencing', 'copy number variation', 'single-nucleotide polymorphism', 'microarray analysis', and 'comparative genomic hybridization'. Studies were limited to pregnancy loss up to 20 weeks in humans and excluded if the genetic content included genes that are not lethal in utero, PGD studies, infertility studies, expression studies, aneuploidy with no recurrence risk, methodologies where there is no clinical relevance, and complex genetic studies. The quality of the studies was assessed using a modified version of the Newcastle–Ottawa scale. OUTCOMES: A total of 50 studies were identified and categorized into three themes: whole-exome sequencing studies; copy number variation studies; and other studies related to pregnancy loss including recurrent molar pregnancies, epigenetics, and mitochondrial DNA aberrations. Putatively causative variants were found in a range of genes, including CHRNA1 (cholinergic receptor, nicotinic, alpha polypeptide 1), DYNC2H1 ( dynein, cytoplasmic 2, heavy chain 1), and RYR1 ( ryanodine receptor 1), which were identified in multiple studies. Copy number variants were also identified to have a causal or associated link with recurrent miscarriage. WIDER IMPLICATIONS: Identification of genes that are causative of or predisposing to pregnancy loss will be of significant individual patient impact with respect to counselling and treatment. In addition, knowledge of specific genes that contribute to pregnancy loss could also be of importance in designing a diagnostic sequencing panel for patients with recurrent pregnancy loss and also in understanding the biological pathways that can cause pregnancy loss.